Spornosexual Capital: The Economic Crisis of Indonesian Urban Masculinity - Dian Arymami (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2020)
The emergence of new digitally mediated body practices among the young, middle class, and male is evidence of a recent shift in the modern power hierarchy. An increasing number of men go to the gym and share pictures of their bodies that had begun globally around 2008. This coincides with the intensification of neoliberalism that cannot be separated from the massive development of digital communication. This phenomenon is also evident in developing in Indonesia, giving birth to new forms of male body mediation. This research explores how spornosexual men mediate their bodies publicly with the shift in digital neoliberal culture. By using the reception analysis through interviews, this study takes five spornosexual people in deciphering neoliberal interconnection through the use of the body as capital. The results show spornosexual has become a new capital amidst our daily lives today.